Omtrent Tekenkunst : Hedendaagse Tekenvormen. - Sint-Lukasgalerij, Brussel (Brussel : Sint-Lukasgalerij, 1987)
Ampe, Dominique ; Beyls, Peter ; Blondeel, Maria ; Boulanger, Michel ; Charlier, Jacques ; Claus, Luc ; Coeckelberghs, Luc ; Coolens, Wouter ; Coopers, Leo ; De Greef, Rudolf ; Deleu, Luc ; De Man, Petrus ; De Smet, Eric ; Desmet, Theresa ; De Vos, Danny ; Dondeyne, Luc ; etc.
Omtrent Tekenkunst : Hedendaagse Tekenvormen, Sint-Lukasgalerij, Brussel, 12.02.1987 - 06.03.1987
boek